FAMILY-BASED TREATMENT FOR ADOLESCENT ANOREXIA NERVOSA – A NARRATIVE REVIEW - SVETLANA OSHUKOVA, JAANA SUOKAS (Psychiatria Fennica)
ABSTRACT Eating disorders (EDs), including anorexia nervosa (AN), bulimia nervosa (BN) and others, are serious mental illnesses that often begin in adolescence and early adulthood. EDs are associated with serious medical and psychological consequences and are considered difficult to treat. Family therapy has been a mainstay of treatment for children and adolescents with AN and other EDs for over 30 years. Among the family-focused treatment modalities, a manualized approach called familybased treatment (FBT) has gained the most evidence of efficacy. This model emphasizes parental support in the process of normalization of eating behaviours. Research findings indicate that FBT can lead to significant clinical improvement in three-fourths of young AN patients, with approximately 40% of adolescents achieving full remission following FBT. The aim of this review is to describe the main principles of FBT, to review current research on its effectiveness and outcome predictors, and to briefly describe two potentially effective variants of FBT - multi-family therapy (MFT) and parent-focused treatment (PFT). The authors also share their experience of implementing FBT at the Eating Disorder Unit of Helsinki University Hospital and discuss some aspects of its implementation in Finland.